2022
DOI: 10.3390/ijerph191610054
|View full text |Cite
|
Sign up to set email alerts
|

White Light-Photolysis for the Removal of Polycyclic Aromatic Hydrocarbons from Proximity Firefighting Protective Clothing

Abstract: The presence of polycyclic aromatic hydrocarbons (PAHs) on firefighters’ personal protective equipment is a concern. One form of preventing from these compounds is to decontaminate proximity firefighting protective clothing (PFPC). Traditional decontamination methods do not promote total removal of pollutants and alter the properties of PFPC. The objective of this work was to evaluate the effectiveness of white light-photolysis (WLP), an advanced oxidation process (AOP), for removing PAHs from PFPC, while main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The influences of light intensity, spectrum, and colour temperature have been extensively investigated in the current literature [ 1 , 2 , 3 , 4 , 5 ]. The research findings have been widely applied in a variety of fields, including medicine, transportation, and marketing communication [ 6 , 7 , 8 ]. Hartstein et al found that adolescents exposed to low correlated colour temperature (CCT) had better sleep quality and were less exhausted the next day [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The influences of light intensity, spectrum, and colour temperature have been extensively investigated in the current literature [ 1 , 2 , 3 , 4 , 5 ]. The research findings have been widely applied in a variety of fields, including medicine, transportation, and marketing communication [ 6 , 7 , 8 ]. Hartstein et al found that adolescents exposed to low correlated colour temperature (CCT) had better sleep quality and were less exhausted the next day [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silerio-Vázquez et al [16] analyzed a solar heterogeneous photocatalytic (HP) process for arsenite (AsIII) oxidation and coliform disinfection from a real groundwater matrix employing two reactors-a flat-plate reactor (FPR) and a compound parabolic collector (CPC)-with and without added hydrogen peroxide (H 2 O 2 ). Arouca et al [17] evaluated the effectiveness of white-light photolysis (WLP) via an advanced oxidation process (AOP) for removing polycyclic aromatic hydrocarbons (PAHs) from proximity firefighting protective clothing (PFPC), while maintaining the integrity of the fabric fibers. Experiments were carried out, with variations in the reaction time and the concentration of H 2 O 2 .…”
mentioning
confidence: 99%